Continuous equilibrium under base preferences and attainable initial endowments - Ulrich Horst; Michael Kupper; Andrea Macrina; Christoph Mainberger (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
We consider a full equilibrium model in continuous time comprising a finite number of agents and tradable securities.We show that, if the agents' endowments are spanned by the securities and if the agents have entropic utilities, an equilibrium exists and the agents' optimal trading strategies are constant. Affine processes, and the theory of information-based asset pricing are used to model the endogenous asset price dynamics and the terminal payoff. Semi-explicit pricing formulae are obtained and applied to numerically analyze the impact of the agents' risk aversion on the implied volatility of simultaneously-traded European-style options.
Keywords: C62; D52; D53; 330; continuous-time equilibrium; CAPM; affine processes; information-based asset pricing; implied volatility; Optionspreistheorie; Kapitalmarkttheorie; Wertpapierhandel; Gleichgewicht; Capital Asset Pricing Model; Volatilität; Theorie